Answer:
(x - 1)
Step-by-step explanation:
Given
8x² - 15x + 7
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term
product = 8 × 7 = 56 and sum = - 15
The factors are - 8 and - 7
Use these factors to split the x- term
8x² - 8x - 7x + 7 ( factor the first/second and third/fourth terms )
= 8x(x - 1) - 7(x - 1) ← factor out (x - 1) from each term
= (x - 1)(8x - 7) ← in factored form
The missing factor is (x - 1)